Age-related changes in marathon running performances - Lepers, R.; Cattagni, T. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
Older (or masters) endurance athletes are a positive example of exceptional aging and are a rich source of insight into a person`s ability to maintain peak physical performance and physiological function with advancing age (1, 2). Previous studies suggested that the performance of masters runners (> 40 yrs) during marathon running has improved (3). To date, it is not known whether masters athletes still improve their marathon performance or whether they have reached their limits. Accordingly, the purpose of this study was to examine the changes in participation and performance of masters athletes at the New-York City (NYC) marathon over the last 30 years (from 1980 to 2009). Averaged running time performances of the top 10 finishers of each age group (between 20 and 79 yrs of age) for both females and males were analyzed. Gender differences in performance times were also analysed for the top 10 male and female runners between 20 and 65 yrs of age. Over the three decades 1980-89, 1990-99 and 2000-09, the percent of finishers younger than 40 yrs significantly decreased (P < 0.05), while the percent of masters finishers significantly increased (P < 0.05), for both males and females. Over the 3 decades, male masters athletes represented 36%, 45% and 53% of total male finishers, respectively; while female masters athletes represented 24%, 34% and 40% of total female finishers, respectively. For males, mean finish times did not change over the three decades for age groups < 60-64 yrs. In contrast, running times significantly decreased (P < 0.01) over the three decades for age groups > 60-64 yr. Average running time of males within the 70-74 yrs age range significantly decreased (P < 0.01) by 13 min (4.9%) between 1980-89 and 1990-99, and by 4 min (1.6%) between 1990-99 and 2000-09. For females, mean finish times did not change over the three decades for age groups < 45-49 yrs, except the time of the 30-39 yrs group that was lower in 2000-09 decade compared to previous decades. Female running times significantly decreased (P <0.01) over the three decades for age groups > 45-49 yr. Average running times of females within the 60-64 yrs age range significantly decreased (P < 0.01) by 16 min (6.8%) between 1990-99 and 2000-09. These data suggest that male (> 65 yrs) and female (> 45 yrs) master runners have probably not yet reached their limits in marathon performance. The relative stability of gender differences in marathon running times across the different age groups over the last decade also suggests that age-related declines in physiological function do not differ between male and female marathoners. Literature on the masters athletes improvements in performance has already and, should still stimulate further research on the understanding of age related physiological changes and the potential slowing of some of the aging processes through athletic training.